Deliberately inflicted, penetrating injuries of the maxillofacial region (Jael's syndrome). Report of 4 cases - Harris, A M; Wood, R E; Nortjé, C J; Grotepass, F (Journal of cranio-maxillo-facial surgery, 1988)
Four cases of intentional knife wounds of the maxillofacial region are presented. In all instances the patients were conscious at the time of admission, with a knife blade in situ. Treatment consisted of simple removal of the knife. Post surgical recovery was rapid and uneventful. No fatalities resulted and no permanent vascular or neurological damage occurred.